Potential Modulation of Phytochemical Bioavailability by Furanocoumarins from Citrus × paradisi - Luca Bolognini (Nutrimentum et Curae, 2025)
The in vivo efficacy of dietary phytochemicals, known for their antioxidant, anti-inflammatory, and neuroprotective properties, is often limited by poor bioavailability. This constraint largely arises from cytochrome P450 3A4 (CYP3A4)-mediated enzymatic metabolism. This review explores the potential of furanocoumarins from grapefruit (Citrus × paradisi Macfad.) to modulate the bioavailability of phytochemicals by inhibiting CYP3A4. A narrative review of the literature was conducted. The PubMed database was searched up to December 2024 using the keywords “phytochemistry,” “grapefruit juice,” “furanocoumarins,” “bioavailability,” and “CYP3A4”. Inclusion criteria were peer-reviewed English language articles with full-text availability. These publications were required to directly address either phytochemical bioavailability or the effects of grapefruit juice. The literature indicates that furanocoumarins in grapefruit juice are potent inhibitors of intestinal CYP3A4. This inhibition significantly impacts the metabolism of various drugs. While extensive research exists on drug-food interactions, studies on the interaction between furanocoumarins and food-derived phytochemicals are limited. The significant inhibitory effect of grapefruit juice on CYP3A4 suggests a potential for modulating the bioavailability of dietary polyphenols metabolized by this enzyme. Further research is warranted to explore specific polyphenol-CYP3A4 interactions to optimize phytochemical bioavailability for therapeutic benefits. Concurrently, it is imperative to consider potential risks in individuals taking CYP3A4-metabolized drugs.